Parker looks up : an extraordinary moment - Curry, Parker; Curry, Jessica (Aladdin, 2019)
"This book is based on the viral photograph of African American toddler Parker Curry, who, during a visit to the National Portrait Gallery, became mesmerized by Amy Sherald's portrait of Michelle Obama, who she thought was a queen"--